Unconditional Bases of Systems of Bessel Functions - Vynnyts’kyi, Bohdan; Khats’, Ruslan; Sheparovych, Iryna (Eurasian Mathematical Journal, 2020)
We find a criterion of unconditional basicity of the system (√xρkJν(xρk) : k ∈ N) in the space L2(0; 1) where Jν is the Bessel function of the first kind of index ν ≥ -1/2 and (ρk : k ∈ N) is a sequence of distinct nonzero complex numbers.